A Remotely Actuated Multifunctional Nitinol–PMMA Smart Biocomposite: Microcellular Foaming, Shape Morphing, and Controlled Drug Release - Lim, Donghwan; Kim, Jaehoo; Kim, Tae Young; Kwon, Jiwon; Kim, Jaewoo; Seo, Jungmok; Jang, Yong Hoon; Cha, Sung Woon; Yoon, Jun Young (American Chemical Society, 2025)
The fabrication of smart biomaterials that can perform precisely controlled multifunctional tasks in vivo is a significant and challenging goal in therapeutic medicine. Therefore, a remotely actuated, multifunctional smart biocomposite was fabricated herein using Ni–Ti alloy (Nitinol) and poly(methyl methacrylate) (PMMA). The Nitinol–PMMA composite achieved three distinct functions: shape morphing, microcellular foaming, and drug release. Under a noncontact electromagnetic field, the smart biocomposite underwent simultaneous preprogrammed shape morphing due to the heating of Nitinol and microcellular foaming in the carbon dioxide (CO2)-saturated PMMA. This foaming enhanced the impact strength of the composite by 143% and enabled the controlled release of preloaded agents such as sodium benzoate (NaBz) from the PMMA matrix. The potential of the Nitinol–PMMA composite for vascular clamping was confirmed in an in vitro environment, wherein it exhibited excellent cytocompatibility with NIH 3T3 fibroblasts. The kinetic analysis of NaBz release using the Korsmeyer–Peppas model confirmed that the drug release was governed by a quasi-Fickian mechanism correlated to the porosity of the material. This remotely actuated system that integrates actuation, microbubble control, and customized therapy via tailored drug delivery represents a promising paradigm for the development of minimally invasive medical devices.